Avaliação das condições operacionais na taxa de evaporação de água em leito de jorro - Bitti, Maisa Tonon (2012)
In this work, the influence of operating conditions on the evaporation rate of water was analyzed for drying in a spouted bed. Experiments were done for two different inlet air geometries and inert particles loads for variable paste feed flow rates and inlet air temperature and velocity. Distilled water was employed as standard paste and glass beads of 2,18mm and 2512,6 ± 0,1kg/m3 as the inert phase. The drying chamber consisted essentially of an inox cylindrical column with 120cm in height and 30cm in diameter, and a conical bottom with an angle of 60° and 23cm high. The orthogonal central composite design was used to specify the experimental conditions. Inlet air temperature and velocity, bed pressure drop, exhaust temperature and dry and wet bulb temperature at the cyclone were measured during the experiments. Results have showed that the inlet air geometry had a weak influence on the bed fluidynamic stability. The maximum evaporation rate for both inlet air geometries was of 60ml/min, under operating conditions of 115ºC 1,55u/ujm and for 8,5kg particle load. An experimental correlation was proposed to estimate de rate of water evaporation as a function of the independent variables considered. With the experimental design analysis on the water evaporation rate it was possible to identify the most significant factors that influence the process. The information obtained in this work may be the basis for future work in this field with real pastes.